78 Changing minds, saving limbs; reforming referral pathways in critical limb ischaemia. (12th November 2018) - Dadabhoy, Maria; Nair, Darshana; Light, Alexander; Khanna, Angela; Wojtaszek, Mikolaj
Abstract : Background: Critical limb ischaemia (CLI) is a limb and life-threatening condition. Current NHS guidelines suggest that suspected CLI patients should be assessed by a vascular nurse practitioner (VNP) within 7 days of GP-presentation. Any indicated procedure should then be performed within the following 6 weeks. Retrospective review of patient records (n=9) at this Trust showed that mean time from GP presentation to VNP review was 8.1±3.1 weeks, with a subsequent procedure requiring further 15.8±5.2 weeks. Aim: To design referral pathways that the Trust believes will lead to CLI patients receiving vital treatment sooner. Methods: Baseline surveys were obtained from 14 stakeholders to assess perceptions of current referral pathways. Our survey comprised 10 questions, assessed using a five-point Likert scale (maximum score 50), with a higher score indicating greater confidence in the system. We also designed new pathways in conjunction with a new tiered scoring system to assess disease severity. Using Plan-Do Study-Act (PDSA) cycles, we then presented these to the same stakeholders, and further reformed our pathways based on feedback. Overall, we completed 2 PDSA cycles, presenting to a senior VNP, and then to the vascular multidisciplinary team meeting. Results: We designed 3 new referral pathways, 'red', 'amber' and 'green'. Each pathway had a different proposed timeline corresponding to patient disease severity, as assessed using our tiered scoring system. Baseline mean survey score was 25.4±2.3, and final mean score was 33.9±5.2. This represented a significant improvement in stakeholder confidence (Wilxocon Signed-Ranks test, p=0.003). Conclusions: Improving perceptions of necessary change is an important step to implementing such change. It is necessary to build a culture of improvement prior to implementing any. We have designed new CLI referral pathways that are perceived to be superior to the current pathways. Although further refinement is likely necessary, we believe these pathways are suitable for implementation in the near future.